مساهمة التسويق الداخلي في المشاركة المعرفية - منال, دونة; مريم, بوزنادة (University of eloued جامعة الوادي, 2020)
"تعد المشاركة المعرفية من المفاهيم الجوهرية في المنظمة، لأجل ذلك تبدأ في تسييرها للمعرفة من التسويق الداخلي وتحاول جاهدة لإيجاد الأساليب المناسبة التي تمكنها من فهمه والتحكم فيه حتى تتمكن من تفعيله والاستثمار فيه، لذا جاءت هذه الدراسة لإظهار مدى المساهمة التي يحدثه التسويق الداخلي بأبعاده (التدريب، التحفيز والاتصال الداخلي) في المشاركة المعرفية في الصندوق الوطني للتأمينات الاجتماعية للعمال الأجراء بولاية الوادي، بالاعتماد على تقنية دراسة الحالة مستخدمين الاستبيان كأداة لجمع المعلومات، فقمنا بتوزيعه على عينة عشوائية مقدارها 40 عامل، وكان عدد الاستبيانات المسترجعة والصالحة للتحليل الإحصائي35 استبيان، استخدم في التحليل الإحصائي للبيانات عدة أساليب إحصائية. حيث أظهرت الدراسة بأنه باستثناء الاتصال الداخلي وجد بأن كل من التدريب والتحفيز يساهمان في المشاركة المعرفية، وأثبتت الفرضية الرئيسية للدراسة صحتها والتي ترى بأن التسويق الداخلي يساهم في المشاركة المعرفية. ولقد خلصت الدراسة بنتيجة مفادها وجود علاقة إيجابية بين التسويق الداخلي والمشاركة المعرفية. ""Knowledge sharing is a core concept in the organization. It starts to run knowledge from internal marketing and tries to find the appropriate ways to understand and control it to activate and invest in it. This study shows how much internal marketing contributes with its dimensions (training, motivation and intercom) to the knowledge participation in the National Fund for Social Insurance for workers in El-OUAD State, using the case study method by distributing questionnaires as a tool for collecting information. A random sample of 40 workers received questionnaires. The number of questionnaires returned and valid for statistical analysis was 35. Several statistical methods were used to analyze data. The study showed that, except intercom, both coaching and motivation contributed to cognitive engagement, and the central hypothesis of the study proved correct. Internal marketing contributes to cognitive engagement. The study concluded that there was a positive relationship between internal marketing and cognitive engagement. "
مذكرة ماستر ادارة اعمال
Keywords: التسويق الداخلي- المشاركة المعرفية- التدريب- التحفيز- الاتصال الداخلي; Internal Marketing- Knowledge Sharing- Traning- Motivation- Intercom Productivity